Recognition of hepaciviruses by ficolins in different mammalian species - Adedeji, Yemisi Oluwatomi (2020)
Ficolins are polymorphic liver-expressed pattern recognition receptors (PRRs) that contribute to the innate surveillance of virus infections, recognising carbohydrates such as N-acetyl glucosamine, which are components of glycoproteins found on the surface of different viruses. While human ficolin-2 has been demonstrated to bind and inhibit entry of hepatitis C virus (HCV) particles, the antiviral activity of ficolins found in other mammalian species is unknown. For the first time, recombinant mouse and non-human primate (NHP) ficolins were cloned, expressed and purified to determine their interaction with HCV and non-primate/Equine hepacivirus (NPHV/EqHV), and the impact on virus entry. HCV and EqHV have been recently reported as closely related within the hepacivirus genera (family Flaviviridae). This relatedness may provide insights on the potential use of EqHV as a model for the study of HCV. Both viruses encode two glycoproteins (E1 and E2), which are found on the surface of the viral envelope. These glycoproteins facilitate the entry into the host and are targets for host immune recognition molecules like ficolins. HCV and EqHV pseudoparticles (pp) were used to determine the neutralising ability of ficolins from different species. An EqHVpp model system for the investigation of entry and neutralisation of EqHV infection was created and validated. In this study, for the first time, the neutralisation of hepacivirus by non-human ficolins was assessed. These findings may provide better insight into the divergent evolution of these genes in mammals. It is possible that ficolins might serve as a future therapeutic anti-viral agent for hepaciviruses.